Housing markets in selceted European countries and the USA - Magdalena Gostkowska-Drzewicka (e-Finanse: Financial Internet Quarterly, 2012)
The aim of this article is to present the changes taking place in housing markets in selected European countries and in the USA. The basic research period covers the years 1998-2009. However, wherever availability of data allowed so, we covered with our research also the years 1963-2010. The development of domestic housing markets is determined both by specific features of local markets and by macroeconomic factors influencing the economic situation. The availability of capital to finance investment is of primary importance for the changes taking place in housing markets. This factor can be expressed by the volume of mortgage debt related to GDP and inflation and the level of interest rates on mortgage loans. The evaluation of the changes occurring in domestic housing markets was based on the identification of such structural characteristics as: the volume of the housing stock, the number of ready-to-use flats, the number of issued building permits, the indices of housing prices, and the number of transactions concerning purchase of flats or houses.
Keywords: R31; 330; real estate market; dwellings; mortgage loans